Common Coupled Fixed Points of a Pair of Compatible Mappings satisfying the Condition (B) with a Rational Expression in Partially Ordered Metric Spaces: G. V. R. Babu, Y. J. Cho, M. V. R. Kameswari - Team, Support (Thai Journal of Mathematics, 2015)
The aim of this paper is to prove the existence of common coupled coincidence points and common coupled xed points for a pair of compatible maps satisfying condition (B) with a rational expression in partially ordered metric spaces. Further, we discuss the importance of rational expression in condition (B). Our results extend and improve the results of Luong and Thuan[16], generalize the results of Lakshmikanthamand Ciric[17] and Saud and Abdullah [2].